Owning the masters a history of sound recording copyright - Osborne, Richard 1967- (Bloomsbury Academic, a trademark of Bloomsbury Publishing Plc, 2023)
"The story of how record companies gained ownership of sound recording rights and examines the consequences of this ownership for musical creation and reception"--Provided by publisher.